Analysis of Spatial Data Infrastructure (SDI) to Support Tourism Village Promotion in Badung Regency, Bali, Indonesia - I Ketut Sardiana; Ni Luh Ramaswati Purnawan; Putu Perdana Kusuma Wiguna; R. Suyarto; Tati Budi Kusmiyarti (Faculty of Geography, Universitas Gadjah Mada, 2021)
Indonesia’s Tourism Law No. 10 of 2009 states that tourism development needs to integrate diversity, culture and nature uniqueness, and demands. As a popular tourist destination, Badung Regency (Bali, Indonesia) shows similar tourism development across its tourist attractions. Therefore, it is necessary to make a breakthrough in alternatives, including a tourist village. This study aimed to analyze the Spatial Data Infrastructure (SDI), including data, standards, policies, technology, and human resources, to promote tourism villages in the area. The WebGIS-based Tourism Geoportal is a technology built to inform tourists, local communities, tourism associations, and local governments. The results showed that, as yet, the Badung Regency Government was not entirely ready to implement SDI to promote tourism villages. Overall, no standards and policies are governing SDI. In addition, the human resources are limited and not specially trained to organize and operate SDI. The available data are relatively complete but are missing metadata and lacking information on attribute data. Testing of the geoportal as a promotional tool for the tourism villages resulted in an agreement on the benefits of SDI to support the development of tourist villages and the importance of establishing local regulations and standards and improving the quality of human resources.